CONSTITUTIONAL MORALITY AND SOCIETAL MORALITY: AN IMPACT OVER LIVE IN RELATIONSHIP - Panwar, Prashant; Lamba, Kirty; Dixit , Ravi Kant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The article’s primary concern is the current situation of constitutional and societal morality and how it pertains to all contemporary societies. Since morality is, as we all know, the basis of law, the concept of morality is represented by a law. The concept of a live-in relationship is among the constitutionality and cultural morality issues that need to be addressed. Although the notion of a live-in relationship is protected by Article 21 of the Indian Constitution When seen in the context of Indian society, it transcends the scope of social morality as an issue of constitutional morality. The study examines the differences between and relationships between constitutional morality and societal morality, as well as how this impacts romantic relationships. In line with the proverb, A civilization may only grow if it adapts to its environment, broadens the concept of public morality, and accepts novel ideas like live-in relationships. The objective of this study is to strike a balance between constitutional and cultural morality in order to recognise the idea of a live-in relationship without restricting itself to morality’s tenets.